Review Penentuan Residence Time Partikel pada Perairan - Wahyuni, Dwi Sukma Wahyuni; Kisnarti, Engki A Kisnarti (Universitas Hang Tuah, 2023)
Residence time is the length of time a particle lives in water. Particle movement can be analyzed by using current circulation parameter. This research study aims to determine and describe the length of time the particles stay in the waters. The models used to determine particle movement are hydrodynamic numerical models, especially the Lagrange Finite Volume Coastal Ocean Model (FVCOM) and CRT (Coastal Residense Time) models. In describing the movement of particles modeled using Mike 21 FM. The results from the CRT model with high resolution have a smaller error value, compared to using the FVCOM model. The characteristics of the CRT itself use a logarithmic method so that it has the same grid to determine the length of residence time of the particles.